A set oriented approach to optimal feedback stabilization - Grüne, Lars; Junge, Oliver (Systems & Control Letters)

A Survey of Methods for Computing (un)stable Manifolds of Vector Fields - Krauskopf, B.; Osinga, H. M.; Doedel, E. J.; Henderson, M. E.; Guckenheimer, J.; Vladimirsky, A.; Dellnitz, M.; Junge, O. (International Journal of Bifurcation and Chaos)
The computation of global invariant manifolds has seen renewed interest in recent years. We survey different approaches for computing a global stable or unstable manifold of a vector field, where we concentrate on the case of a two-dimensional manifold. All methods are illustrated with the same example — the two-dimensional stable manifold of the origin in the Lorenz system.

Satellite Formation, a Mobile Sensor Network in Space - Krishnamurthy, A.; Preis, R. (19th IEEE International Parallel and Distributed Processing Symposium)

Design and implementation of a hybrid energy supply system for railway vehicles - Li, R.; Pottharst, A.; Frohieke, N.; Becker, J.; Witting, K.; Dellnitz, M.; Znamenshchykov, O.; Feldmann, R. (Twentieth Annual IEEE Applied Power Electronics Conference and Exposition, 2005. APEC 2005.)

Aktuelle Entwicklung im europäischen Bank- und Kapitalmarktrecht - Krimphove, Dieter (Zeitschrift für das gesamte Kreditwesen)

Covering Pareto Sets by Multilevel Subdivision Techniques - Dellnitz, M.; Schtze, O.; Hestermeyer, T. (Journal of Optimization Theory and Applications)

Regulierung und Haftung von Ratingagenturen: Status quo und Perspektiven - Krimphove, Dieter; Kruse, Oliver (Zeitschrift für das gesamte Kreditwesen)

Rechts- und Haftungsfragen des externen Unternehmensratings - Krimphove, Dieter (Finanz Betrieb)

ARIDA - Eine Abstraktion von Eingabegeräten zur Verwendung in augmented Reality Anwendungen, Virtuelle und Erweiterte Realität - Redmer, B.; Goetz, F.; Domik, Gitta

Integration of Point Based Rendering into a Common Scene Graph System - Goetz, F.; Hillebrand, L.; Domik, Gitta (the 5th IASTED International Conference on Visualization, Imaging, and Image Processing)